Correlation of ovarian adnexal reporting and data system classification with histopathological examination in diagnosis of adnexal masses - Takkar, Navneet; Arora, Pallavi; Goel, Bharti; Kaur, Ravinder; Kaur, Narinder; Aggarwal, Phiza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adnexal masses are common and present significant clinical challenges related to diagnostic imaging, surgery and pathology. Ovarian adnexal reporting and data system (O-RADS) serves as both a lexicon and risk stratification tool, which is designed to accurately characterize adnexal lesions and facilitate optimal patient management. This study aimed to evaluate the diagnostic accuracy of O-RADS using histopathological examination as the gold standard. Methods: This was a prospective observational study conducted in the department of Obstetrics and Gynaecology, Radio-diagnosis, Pathology in collaboration with the department of radio-diagnosis and pathology at Government Medical College and Hospital, Chandigarh from December 2022 to March 2024. A total of 35 women who were diagnosed with adnexal masses were included in the study. Results: The age group of presentation of adnexal masses in our study was 14 to 62 years of age with a mean age of 31.69±11.25 years. O-RADS score 2 was 100% sensitive and 21.4% specific for detecting benign adnexal masses. ORADS score 3 was 100% sensitive and 24% specific for detecting benign masses. O-RADS score 4 was 25% sensitive and 89.47% specific for detecting malignant adnexal masses. Similarly, ORADS score 5 was 100% sensitive and 87.88% specific for detecting malignant masses using histopathology as the gold standard. Conclusions: The ORADS classification system has a high sensitivity in differentiating between benign and malignant lesions when correlated with gold standard histopathology report.